2016
DOI: 10.3390/ijms17040455
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis in HCV Monoinfected and HIV/HCV Coinfected Patients: Dysregulation of Matrix Metalloproteinases (MMPs) and Their Tissue Inhibitors TIMPs and Effect of HCV Protease Inhibitors

Abstract: An imbalance between matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) may contribute to liver fibrosis in patients with hepatitis C (HCV) infection. We measured the circulating levels of different MMPs and TIMPs in HCV monoinfected and HIV/HCV coinfected patients and evaluated the potential for anti-HCV therapy to modulate MMP and TIMP levels in HCV subjects. We analyzed 83 plasma samples from 16 HCV monoinfected patients undergoing dual or triple anti-HCV therapy, 15 HIV/HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 32 publications
1
32
1
3
Order By: Relevance
“…53,54 Thus, MMP-2-deficient mice show enhanced fibrosis after CCL 4 treatment and MMP-2 could be therefore critical for inhibiting type I collagen synthesis by activated HSCs, which strongly express this MMP. 55,56 MMP-9 and MMP-2 are elevated in serum and livers of patients with chronic hepatitis type B and C. [57][58][59] Elevated expression of MMPs in the mentioned fibrotic conditions was shown both in liver parenchyma 60 and portal macrophages. 57,61 Especially, MMP-9 seems to be involved in ongoing liver inflammation, 62 and its level drops after antiviral treatment.…”
Section: Metalloproteinases In the Development Of Liver Fibrosismentioning
confidence: 97%
See 3 more Smart Citations
“…53,54 Thus, MMP-2-deficient mice show enhanced fibrosis after CCL 4 treatment and MMP-2 could be therefore critical for inhibiting type I collagen synthesis by activated HSCs, which strongly express this MMP. 55,56 MMP-9 and MMP-2 are elevated in serum and livers of patients with chronic hepatitis type B and C. [57][58][59] Elevated expression of MMPs in the mentioned fibrotic conditions was shown both in liver parenchyma 60 and portal macrophages. 57,61 Especially, MMP-9 seems to be involved in ongoing liver inflammation, 62 and its level drops after antiviral treatment.…”
Section: Metalloproteinases In the Development Of Liver Fibrosismentioning
confidence: 97%
“…55,56 MMP-9 and MMP-2 are elevated in serum and livers of patients with chronic hepatitis type B and C. [57][58][59] Elevated expression of MMPs in the mentioned fibrotic conditions was shown both in liver parenchyma 60 and portal macrophages. 57,61 Especially, MMP-9 seems to be involved in ongoing liver inflammation, 62 and its level drops after antiviral treatment. 57,63 Induction of MMP-2 is significantly stimulated in the liver of HCV-infected patients.…”
Section: Metalloproteinases In the Development Of Liver Fibrosismentioning
confidence: 97%
See 2 more Smart Citations
“…They are expressed during HSC activation after liver injury. They are considered the putative target of STAT3, and high expressions were observed in hepatic fibrosis patients, liver fibrosis animal models, and activated HSCs [61]. This study demonstrated that MMP-2 and MMP-9 were increased in TGF-β1-activated HSCs, and C7A significantly inhibited its expression, which imply that C7A potentially reduces cell migration and proliferation of activated HSCs.…”
Section: Discussionmentioning
confidence: 66%